2017
DOI: 10.4258/hir.2017.23.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Usages of Computers and Smartphones to Develop Dementia Care Education Program for Asian American Family Caregivers

Abstract: ObjectivesFamilies of ethnic minority persons with dementia often seek help at later stages of the disease. Little is known about the effectiveness of various methods in supporting ethnic minority dementia patients' caregivers. The objective of the study was to identify smartphone and computer usage among family caregivers of dementia patients (i.e., Korean and Vietnamese Americans) to develop dementia-care education programs for them.MethodsParticipants were asked various questions related to their computer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
0
21
1
Order By: Relevance
“…Findings of the current study suggested that the belief in illness as punishment for sin can be predicted by several demographic characteristics and religiosity factors correlated with negative health outcomes. Holding a negative belief, such as illness as punishment for sin, can lead to painful feelings of stigmatization for oneself and others (Bhatnagar et al, 2017;Hulett et al, 2018;Lee et al, 2017;Selman et al, 2018). Our results are counter to the intentions of religious institutions that seek to provide solace and comfort to their congregations (Subramaniam, Camacho, Carolan, & López-Zerón, 2017).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Findings of the current study suggested that the belief in illness as punishment for sin can be predicted by several demographic characteristics and religiosity factors correlated with negative health outcomes. Holding a negative belief, such as illness as punishment for sin, can lead to painful feelings of stigmatization for oneself and others (Bhatnagar et al, 2017;Hulett et al, 2018;Lee et al, 2017;Selman et al, 2018). Our results are counter to the intentions of religious institutions that seek to provide solace and comfort to their congregations (Subramaniam, Camacho, Carolan, & López-Zerón, 2017).…”
Section: Discussioncontrasting
confidence: 57%
“…Belief in illness due to punishment for sin exists across cultures and religions and can be responsible for disapproving attitudes towards those with a health condition (Abulhul, 2020;Bhatnagar et al, 2017;Hulett et al, 2018;Lee et al, 2017). This phenomenon sometimes is used to justify marginalization and stigmatization of individuals with mental illness, leprosy, physical deformities, and disabilities (Daniel, 1983;Ravindran & Myers, 2012;Rai, Peters, Syurina, Irwanto, Naniche, & Zweekhorst, 2020;Wesselmann & Graziano, 2010).…”
mentioning
confidence: 99%
“…A. Lee et al, 2017;Perrin, 2016), sharing Asian American narratives in video, picture, or e-print may raise awareness about healthy behaviors or chronic conditions. For older adults less familiar with social media or the Internet, collaborative education and resource provision in community settings (e.g., Ma et al, 2015) could be effective.…”
Section: Level 3: Raising Public Awareness and Reducing Stigmamentioning
confidence: 99%
“…Strategies from mental health research also might be applied to physical health-related stigma such as increasing social contact (Corrigan et al, 2012; Pettigrew & Tropp, 2006) with Asian Americans coping with physical health conditions. In this era of increased technology use, with frequent use and acceptability in some Asian communities (J. A. Lee et al, 2017; Perrin, 2016), sharing Asian American narratives in video, picture, or e-print may raise awareness about healthy behaviors or chronic conditions.…”
Section: Recommendations For Demarginalizing the Health-related Needs...mentioning
confidence: 99%
“…It can be performed using various types of media, such as brochures, videos, and audiotapes (Denny et al, 2017;Habibzadeh et al, 2018). Nowadays, video-based information provision using smart devices is on the rise (Lee et al, 2017) or tablet PCs (Kim & Hwang, 2016) thanks to advancements in information technology. Some researchers have found that information provided via video (which combine images and sound) is more effective than is that delivered via print media such as via traditional handouts or brochures, which are frequently used in clinical settings (Dias et al, 2016).…”
Section: Introductionmentioning
confidence: 99%